Dual-source dual-energy CT with additional tin filtration: Dose and image quality evaluation in phantoms and in-vivo - Primak, Andrew N. (2010)
PURPOSE: To investigate the effect on radiation dose and image quality of the use of additional spectral filtration for dual-energy CT (DECT) imaging using dual-source CT (DSCT). MATERIALS AND METHODS: A commercial DSCT scanner was modified by adding tin filtration to the high-kV tube, and radiation output and noise measured in water phantoms. Dose values for equivalent image noise were compared among DE-modes with and without tin filtration and single-energy (SE) mode. To evaluate DECT material discrimination, the material-specific DE(ratio) for calcium and iodine were determined using images of anthropomorphic phantoms. Data were additionally acquired in 38 and 87 kg pigs, and noise for the linearly mixed and virtual non-contrast (VNC) images compared between DE-modes. Finally, abdominal DECT images from two patients of similar sizes undergoing clinically-indicated CT were compared. RESULTS: Adding tin filtration to the high-kV tube improved the DE contrast between iodine and calcium as much as 290%. Pig data showed that the tin filtration had no effect on noise in the DECT mixed images, but decreased noise by as much as 30% in the VNC images. Patient VNC-images acquired using 100/140 kV with added tin filtration had improved image quality compared to those generated with 80/140 kV without tin filtration. CONCLUSION: Tin filtration of the high-kV tube of a DSCT scanner increases the ability of DECT to discriminate between calcium and iodine, without increasing dose relative to SECT. Furthermore, use of 100/140 kV tube potentials allows improved DECT imaging of large patients.